A Study on the Recital Necessities and Challenges of the 5th Generation Wireless Networks - Azhi Aziz Salih (QALAAI ZANIST JOURNAL, 2021)
In the ever-changing digital era, everybody enjoys speed, and more so speedy internet connections. Therefore, as most major telecom service providers are operating around the clock to develop internet connections even faster. The electronic devices human beings have become so dependent on such as smartphones, homes, cars, laptops and watches need stable internet connections. All these innovations require always-on and high-speed internet. The fifth generation (5G) wireless network couldn’t have come at a much better time as devices and vehicular needing such strong connectivity are explosion every nanosecond and there is more technological progress. Taleb (2017) opine that the cellular network infrastructure is seen as one of the missing pieces needed to accelerate the optimization of the existing technology available today. 5G technology promises a future of improved data rates, quality service, decreased latency and improved capacity. It promises recital necessities which will be discussing in the paper under the sustainability and efficiency requirements. The paper will also discourse the challenges that the 5G mobile network architecture faces in its journey to bring the fastest internet connectivity ever seen.